Ultrasonography of the multifidus muscle in student circus artists with and without low back pain: a cross-sectional study - Bianca Rossini; Meagan Anstruther; Daniel Wolfe; Maryse Fortin (BMC, 2023)
Abstract Background Degenerative structural changes and functional deficits of the lumbar multifidus (LM) muscle were observed in athletes with low back pain. While spinal injuries are common in circus artists, there is no information on LM characteristics in this population. The aims of this study were to investigate LM morphology and function and explore the relationship between LM characteristics and low back pain in male and female circus artists. Methods 31 college circus students were recruited. Participants completed an online survey to acquire demographic data and low back pain history. Body composition was measured using multi-frequency bio-impedance analysis. Ultrasound examinations at the fifth lumbar vertebrae in prone and standing positions were performed to assess LM cross-sectional area, echo-intensity, thickness. Independent and dependent t-test assessed the difference between sex and side, respectively. The relationships between measures were assessed with Pearson's correlations. The LM characteristics' difference between artists with and without low back pain (group binary variable) was assessed with Analysis of covariance using lean body mass, height and % body fat as continuous covariates. Results Males had significantly larger LM cross-sectional area, lower echo-intensity and greater thickness change from rest to contracted than females. LM cross-sectional area asymmetry in prone was greater in artists reporting low back pain in the previous 4-weeks (p = 0.029) and 3-months (p = 0.009). LM measures were correlated with lean body mass, height, and weight (r = 0.40-0.77, p ≤ 0.05). Conclusion This study provided novel insights into LM characteristics in circus artists. Greater LM asymmetry was observed in artists with a history of low back pain. In accordance with previous studies in athletes, LM morphology and function were highly correlated with body composition measurements.